Social trust and emotional health in rural older adults in China: the mediating and moderating role of subjective well-being and subjective social status - Hongsheng Chen; Zhenjun Zhu (BMC Public Health, 2021)
Abstract Background China is becoming an aging society. The emotional health of the elderly is gaining importance. Social trust is an important factor affecting emotional health, but existing studies have rarely considered the various effects of different types of social trust on rural elderly emotional health. Few studies have analysed the role of subjective well-being and subjective social status in the relationship between social trust and elderly emotional health. Methods Using the data of the China Labor-force Dynamics Survey 2016 (CLDS 2016) and regression models, this study selected 2084 rural respondents aged 60 years and above to analyse the impact of social trust on their emotional health. Social trust was divided into three categories: trust in family members, trust in friends, and trust in neighbours. This study also examined the mediating and moderating effects of subjective well-being and subjective social status on the relationship between social trust and emotional health. Results Trust in family members was significantly and positively associated with emotional health (coefficient = 0.194, P < 0.01) and subjective well-being (coefficient = 0.177, P < 0.01). Trust in friends was significantly and positively associated with emotional health and subjective well-being (coefficient = 0.097, P < 0.01; coefficient = 0.174, P < 0.01, respectively). Trust in neighbours was significantly and positively associated with emotional health and subjective well-being (coefficient = 0.088, P < 0.01; coefficient = 0.177, P < 0.01; respectively). Subjective well-being effectively reduced the impact of social trust in family, friends, and neighbours on the emotional health of the elderly by 0.023, 0.022, and 0.023, respectively. Trust in friends and neighbours significantly and positively affected respondents’ subjective social status (coefficient = 0.120, P < 0.05; coefficient = 0.090, P < 0.10; respectively). Subjective social status effectively reduced the impact of social trust in friends and neighbours on the emotional health of the elderly both by 0.004. The positive relationship between trust in family members and emotional health is weakened by subjective well-being. Conclusions Social trust, especially family relationships, play an important role in maintaining the emotional health of the rural elderly. In response to population ageing, more social policies must be introduced to care for the rural elderly and help them lead a happy and satisfactory life.